Pengaruh Pemaparan Logam Berat Pb (Timbal) Terhadap Perubahan Warna dan Peningkatan Persentase Anakan Jantan Daphnia spp. [Effect Of Heavy Metal Pb (Lead) Expossure To The Color Change and Increase The Percentage Of Male Offsprings Of Daphnia spp. ] - A. Shofy Mubarak,; Akhsan Panna; Yeni Dhamayanti (Faculty of Fisheries and Marine Universitas Airlangga, 2009)
AbstractPb (lead) was a metal that does'nt regulated by water organisms so that the metal was constantly acumulated in organisms tissue. Currently, the pollution Pb in the waters of Indonesia have exceeded the maximum threshold of pollution defined by the government.Daphnia spp. is the organism that have been developed as a bioassay in some developed countries like U.S. and Japan because it has a rapid life cycle that is about three weeks, are sensitive to the chemical in the waters ecology and has an important role in the ecology of freshwater as the first of trophic level in the waters ecology. Target of this research is to obtain information about the concentration of heavy metals Pb that correlated with of Daphnia spp. color changes and increase of male offsprings of Daphnia spp.. This research was th thconducted on november 24 , 2008 until December 8 , 2008 in the Laboratory Education of fisheries, Faculty of Fisheries and Marine, Airlangga University. This research use method of experimental design with Completely Randomized Design (RAL) with five treatments and four rerplicates. Treatment A (control), exposure of Pb in concentration 0 mg/L. Treatment B, Pb concentration 0.90 mg/L, Treatment C, Pb concentration 1.8 mg/L, Treatment D, Pb concentration 2.7 mg/L, and Treatment E with Pb concentration 3.63 mg/L. Collected data were analyzed using Analysis of Variance (ANOVA) with error rate or á = 0,05, if there are a different, hence continued with Duncan's Multiple Range Test. Collected data were analyzed again using linear regression graph to estimate the enhanced in every treatment. The results of research indicates that the heavy metal Pb exposure with different concentrations to the adult female Daphnia spp. did not showing significant different of the daphnia spp. color change. This is because the condition of Hypoxia (oxygen deficiency) more dominant than the increase of methyl farnesoate to influence increase of Daphnia spp.'s haemoglobin synthesa. Besides, research also indicates that the heavy metals Pb exposure with different concentrations to the adult sex Daphnia spp. provide a very significant percentage of male Daphnia spp. offsprings. This happens due to the increase of methyl farnesoate in Daphnia spp. inhibit the formation of female sex of Daphnia spp. offsprings by adult Daphnia spp. that expossured by Pb. Result of processing data using linear regression is a formula y = 18.76x + 3.104. this formula can be used to estimate concentration of Pb in water based on percentage of male offsprings of Daphnia spp. Water quality during research showed the waters pH range between 8.2 - 8.5, dissolved oxygen (DO) oranged between 8.0 - 8.5 mg/L, waters temperature was 26 C and ammonia level was 0.03 mg/L. This Conditions of water quality was the optimal conditions to support Daphnia spp. life.